Effectiveness of different exercise therapies in patients with schizophrenia - Qiqi Liu; Zheshuang Li; Hao Zhang; Ruze He; Ruqing Huang; Xin Wu; Jingying Zhang; Xiangdong Han (Medicine, 2026)
Background: Exercise therapy, commonly referred to as a “green prescription,” is gaining recognition as a promising intervention for schizophrenia treatment. With the ongoing expansion of research in this domain, determining the relatively effective exercise therapy for patients with schizophrenia is important. To identify the most effective exercise intervention, we systematically reviewed Chinese and English databases to evaluate its effects on individuals with schizophrenia. Methods: We conducted extensive searches of English and Chinese databases (PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, WanFang Academic Journal Full Text Database [Wanfang], VIP Chinese Science and Technology Periodicals Full-Text Database [VIP], and SinoMed) from the inception of each database until January 30, 2024 (complete search strategies see Table S1, Supplemental Digital Content 1). We assessed the risk of bias in the included studies using the updated Cochrane Risk-of-Bias Tool for randomized controlled trials, with detailed results presented in Table S1, Supplemental Digital Content 1. Furthermore, we ranked the treatment measures using surface under the cumulative ranking curve probability values, and reported effect sizes (standardized mean difference) with 95% confidence intervals for clinical significance judgment. The assessment measures included Positive and Negative Syndrome Scale, Scale for the Assessment of Negative Symptoms, Scale for the Assessment of Positive Symptoms, and Inpatient Psychiatric Rehabilitation Outcome Scale scores. Results: Thirty randomized controlled trials involving 2628 patients and 9 treatments were included. Network meta-analysis showed aerobic exercise (AE), yoga, and tai chi alleviated symptoms. surface under the cumulative ranking curve ranking: AE combined with tai chi may have a higher likelihood of reducing Positive and Negative Syndrome Scale scores (88.2%); yoga may have a higher probability in reducing Scale for the Assessment of Negative Symptoms (89.6%) and Scale for the Assessment of Positive Symptoms (86.7%) scores; tai chi may be more likely in lowering Inpatient Psychiatric Rehabilitation Outcome Scale scores (76.5%). Conclusion: Exercise therapy may exhibit potential efficacy in treating schizophrenia, with AE, yoga, and tai chi exhibiting superior effectiveness compared to control therapies in symptom reduction. However, the certainty of evidence is limited by small sample sizes, heterogeneity in exercise protocols, and moderate risk of bias in some studies. Further validation through rigorous, multicenter, and large-scale clinical trials with standardized exercise protocols is needed.